2017
DOI: 10.3390/genes9010001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Studies of the Effect of nod Gene-Inducing Molecules in Rhizobia: Different Weapons, One Purpose

Abstract: Simultaneous quantification of transcripts of the whole bacterial genome allows the analysis of the global transcriptional response under changing conditions. RNA-seq and microarrays are the most used techniques to measure these transcriptomic changes, and both complement each other in transcriptome profiling. In this review, we exhaustively compiled the symbiosis-related transcriptomic reports (microarrays and RNA sequencing) carried out hitherto in rhizobia. This review is specially focused on transcriptomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 121 publications
0
27
0
1
Order By: Relevance
“…trifolii is a Gram-negative bacterium that exists as a free-living organism in the soil or establishes nitrogen-fixing symbiosis with clover plants ( Trifolium spp.). This microorganism belongs to a large and diverse group of soil bacteria, collectively called rhizobia, which possess the ability to induce nodules on roots and stems of legumes [ 1 , 2 ]. Within nodules, new plant organs ensuring a special ecological niche, rhizobia reduce dinitrogen to ammonia, which is then used by the host plant.…”
Section: Introductionmentioning
confidence: 99%
“…trifolii is a Gram-negative bacterium that exists as a free-living organism in the soil or establishes nitrogen-fixing symbiosis with clover plants ( Trifolium spp.). This microorganism belongs to a large and diverse group of soil bacteria, collectively called rhizobia, which possess the ability to induce nodules on roots and stems of legumes [ 1 , 2 ]. Within nodules, new plant organs ensuring a special ecological niche, rhizobia reduce dinitrogen to ammonia, which is then used by the host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effects of G. max RE on two B. diazoefficiens strains, 4534 and 4222, were analysed by transcriptomics [ 53 ], which showed that several genes coding for two-component systems ( nodW, phyR-σ EcfG ), bacterial chemotaxis ( cheA ), ATP-binding cassette (ABC) transport proteins, and indole-3-acetic acid (IAA) metabolism were upregulated in the more competitive B. diazoefficiens strain 4534. A recent publication of Jiménez-Guerrero and colleagues extensively reviewed the transcriptomic studies performed in alpha-rhizobia with an emphasis on the effect of flavonoids on the activation of nod genes [ 98 ].…”
Section: Functional Genomics Of Rhizobia-legume Symbiosismentioning
confidence: 99%
“…The molecular mechanisms underlying the physiological adaptation of rhizobia in the root nodules have so far been mainly studied in α-rhizobial symbiosis model systems. Several studies have relied on functional genomics technologies like transcriptomics, proteomics and metabolomics, and comparative genomics [11,12,13,14,15,16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%